2008
DOI: 10.1007/s00264-008-0640-x
|View full text |Cite
|
Sign up to set email alerts
|

One-stage cementless revision arthroplasty for infected hip replacements

Abstract: We hypothesised that one-stage cementless revision hip arthroplasty may have advantages and a role in the treatment of selected patients with an infected hip replacement. We retrospectively reviewed all patients with an infected hip replacement treated with one-stage revision using cementless implants. Twelve patients were reviewed and followed up for at least three years (average: 7.2 years, range: 3.3-11.3 years) postoperatively. One recurrence of infection and one aseptic stem loosening were detected during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 24 publications
0
50
0
4
Order By: Relevance
“…If possible, a cementless fixation should be striven for. Clinical results that have been recorded so far are promising for the cementless revision (revision rates of 20% cemented vs. 7% cementless) [3,7,22,23].…”
Section: Discussionmentioning
confidence: 98%
“…If possible, a cementless fixation should be striven for. Clinical results that have been recorded so far are promising for the cementless revision (revision rates of 20% cemented vs. 7% cementless) [3,7,22,23].…”
Section: Discussionmentioning
confidence: 98%
“…Yoo et al [44] published a retrospective review of 12 patients treated with a variety of cementless implants. Eleven had type II infections.…”
Section: One-stage Revisionmentioning
confidence: 99%
“…To date, only one other study has reported outcomes after cementless single-stage exchange arthroplasty for periprosthetic hip infection: in a cohort of 12 patients with chronic PJI, Yoo et al [34] reported component retention in 10 of 12 patients at a mean followup of 7.2 years. However, they excluded all patients with PJI caused by MRSA.…”
Section: Discussionmentioning
confidence: 99%
“…However, several publications have demonstrated a failure rate, as defined as recurrent infection, component removal, or need for additional surgery resulting from infection, of 12% to 86% in series ranging from 20 to 138 patients [1,8,13,18,20,29]. In response to the unpredictability of this approach to control the infection, some have suggested a one-stage exchange arthroplasty as an alternative because it allows more thorough surgical débridement and removal of biofilm-colonized implants [2,4,16,34].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation